2017
DOI: 10.1637/11557-121216-resnote.1
|View full text |Cite
|
Sign up to set email alerts
|

First Report of Avian Metapneumovirus Subtype B Field Strain in a Romanian Broiler Flock During an Outbreak of Respiratory Disease

Abstract: Avian metapneumovirus (aMPV) represents one of the most prevalent diseases of turkey, especially in combination with other pathogens, and its frequency is also increasing among chickens. Despite this evidence, epidemiologic data are poor and scattered, severely preventing control of the disease even in highly developed areas such as Europe. In the present study, the detection and characterization of an aMPV subtype B strain circulating in a vaccinated but symptomatic Romanian broiler flock is reported for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 28 publications
2
8
0
Order By: Relevance
“…The pivotal role of some countries like France and Italy in aMPV-B epidemiology could be linked to the higher number of turkeys, traditionally considered the main viral host species, historically reared in these countries. However, many recent studies have reported a high aMPV detection frequency also in chickens [25][26][27][28] and the present results demonstrate a relevant strain exchange between the two species, making unlikely the preeminent role of turkeys in aMPV epidemiology. Alternatively, the high proportion of sequences obtained from Italy and other countries could have led to an overestimation of their epidemiological role.…”
Section: Discussionsupporting
confidence: 45%
See 1 more Smart Citation
“…The pivotal role of some countries like France and Italy in aMPV-B epidemiology could be linked to the higher number of turkeys, traditionally considered the main viral host species, historically reared in these countries. However, many recent studies have reported a high aMPV detection frequency also in chickens [25][26][27][28] and the present results demonstrate a relevant strain exchange between the two species, making unlikely the preeminent role of turkeys in aMPV epidemiology. Alternatively, the high proportion of sequences obtained from Italy and other countries could have led to an overestimation of their epidemiological role.…”
Section: Discussionsupporting
confidence: 45%
“…Because of their broader distribution and high detection frequency, subtype A and B were long considered a relevant threat for the poultry industry. However, most recent epidemiological studies performed in Europe have consistently reported the absence of aMPV-A, which was clearly outclassed by aMPV-B [ 25 28 ]⁠.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, the parent chicken stocks of the Bovans Brown breeds were imported into Ethiopia from Europe. The introduction of foreign strains could represent a possible route of viral entry for aMPV also, since the subtype B virus is by far the predominant one in Europe [30,63,64]. Other studies are currently ongoing to better characterize aMPV molecular epidemiology in Ethiopia and to understand its clinical and economic relevance.…”
Section: Discussionmentioning
confidence: 99%
“…Despite these reports, molecular data on aMPV strains circulating in Europe are still poor and scattered (Catelli et al., 2004; Cecchinato, Drigo, et al, 2013; Listorti et al., 2014; Franzo et al., 2017; Tucciarone et al., 2017, 2018; Ball, Forrester, & Ganapathy, 2018; Andreopoulou et al., 2019), as most of them originate from few countries. In the last decades, subtype B has been generally the most frequently encountered subtype in Europe, although subtype A has been sporadically reported (Lupini, Cecchinato, Ricchizzi, Naylor, & Catelli, 2011).…”
Section: Introductionmentioning
confidence: 99%